Investor Herding Behaviour in a Frontier Market: Evidence from Dar es Salaam Stock Exchange - Abraham Charles Nathanael; Karoli Calist Chami (Faculty of Economics, Universitas Sriwijaya, 2026)
This paper examines how investors behave in the Dar es Salaam Stock Exchange (DSE), with a focus on their tendency to follow others when making investment decisions. Based on survey data from 356 investors, the study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore how psychological, demographic, and informational factors shape herding behaviour. The results reveal that psychological traits including risk aversion, overconfidence, and trust in peers together with the market information environment, have a strong and significant effect on herding. In contrast, demographic factors such as age, education, and income show only weak influence. In the presence of limited information and uncertainty, psychological biases have more significance, hence making the investors base their decision on the actions of other people instead of their independent analysis. Such collective behaviour creates mispricing in the market, leading to inefficiency and poor investment performance. According to the findings of the paper, information transparency and better awareness of the investors would be effective in preventing herding behaviour.